Factors associated with cortisol levels and health in 5–6‐year‐old children. Issue 5 (1st August 2013) - Cardas, J.; Azpiroz, A.; Pascual‐Sagastizabal, E.; Pérez‐Yarza, E.G.; Etxebarria, A.E.; Azurmendi, A.; Sanchez‐Martín, J.R.
<x xml:space="preserve">Abstract</x> Objectives This study assesses the relationships between social context (family and inter‐peer context), stress, and illness in 5–6‐year‐old children. Methods To this end, data were collected on spontaneous social interpeer behavior; families provided data on stress, anxiety, and parental acceptance‐rejection; and the children's pediatricians provided data relative to their health. Data on stress‐related hormones (cortisol) were collected using saliva samples. Results The results revealed that none of the variables examined were significantly related to illness development in the subjects in the sample group. Cortisol levels, however, were positively associated with a record of chronic or congenital illnesses, the manifestation of behaviors related to the search for leadership status in the group and the presence of stressful events in the family environment. Conclusions Despite finding no relationship between children's level of adrenocortical activity and the contracting or contingent development of diseases, we did find that chronic/congenital diseases may constitute a source of early stress in childhood. Certain conditions of uncertainty in the social context (family and interpeer) also seem to constitute different sources of stress. Am. J. Hum. Biol., 25:606‐616, 2013. © 2013 Wiley Periodicals, Inc.